2020
DOI: 10.36834/cmej.70496
|View full text |Cite
|
Sign up to set email alerts
|

First year medical student experiences with a clinical skills seminar emphasizing sexual and gender minority population complexity

Abstract: Purpose: Patients identifying as sexual and gender minorities (SGMs) face healthcare barriers. This problem is partly due to medical training.1 We evaluated first year medical student experiences during a novel four-hour seminar, in which students answered discussion questions, participated in peer role-plays, and interviewed two standardized patients Method: A constructivist qualitative design employed audio-recorded and transcribed student focus groups. Using generic content analysis, transcripts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The most commonly reported barrier related to the training interventions was lack of appropriate educational materials (Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Vance et al, 2020 , 2021 ). Facilitation-related barriers primarily centered around the lack of expertise or experience among faculty or instructors to facilitate the training (Berenson et al, 2020 ; Biro et al, 2021 ; Block et al, 2020 ; Click et al, 2019 , 2020 ; Greene et al, 2017 ; Marshall et al, 2017 ; McCave et al, 2019 ; Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Sawning et al, 2017 ; Sequeira et al, 2012 ; Stumbar et al, 2021 ; Thompson et al, 2020 ; Ufomata et al, 2020 ; Vance et al, 2018 ) and availability of transgender simulation patients (Berenson et al, 2020 ; Biro et al, 2021 ; Block et al, 2020 ; Click et al, 2019 , 2020 ; Greene et al, 2017 ; Marshall et al, 2017 ; McCave et al, 2019 ; Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Sawning et al, 2017 ; Sequeira et al, 2012 ; Stumbar et al, 2021 ; Thompson et al, 2020 ; Ufomata et al, 2020 ; Vance et al, 2018 ). Low participation rates among certain subgroups (e.g., male and cisgender people) was the most reported barrier related to the audience (Braun et al, 2017 ; Minturn et al, 2021 ; Pathoulas et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly reported barrier related to the training interventions was lack of appropriate educational materials (Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Vance et al, 2020 , 2021 ). Facilitation-related barriers primarily centered around the lack of expertise or experience among faculty or instructors to facilitate the training (Berenson et al, 2020 ; Biro et al, 2021 ; Block et al, 2020 ; Click et al, 2019 , 2020 ; Greene et al, 2017 ; Marshall et al, 2017 ; McCave et al, 2019 ; Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Sawning et al, 2017 ; Sequeira et al, 2012 ; Stumbar et al, 2021 ; Thompson et al, 2020 ; Ufomata et al, 2020 ; Vance et al, 2018 ) and availability of transgender simulation patients (Berenson et al, 2020 ; Biro et al, 2021 ; Block et al, 2020 ; Click et al, 2019 , 2020 ; Greene et al, 2017 ; Marshall et al, 2017 ; McCave et al, 2019 ; Park & Safer, 2018 ; Rosendale & Josephson, 2017 ; Sawning et al, 2017 ; Sequeira et al, 2012 ; Stumbar et al, 2021 ; Thompson et al, 2020 ; Ufomata et al, 2020 ; Vance et al, 2018 ). Low participation rates among certain subgroups (e.g., male and cisgender people) was the most reported barrier related to the audience (Braun et al, 2017 ; Minturn et al, 2021 ; Pathoulas et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Low participation rates among certain subgroups (e.g., male and cisgender people) was the most reported barrier related to the audience (Braun et al, 2017 ; Minturn et al, 2021 ; Pathoulas et al, 2021 ). Institutional/contextual barriers included time constraints in the majority of sources and costs associated with consultation, curriculum development, as well as recruiting and fairly compensating transgender simulation patients/guest speakers (Altneu et al, 2020 ; Bi et al, 2020 ; Biro et al, 2021 ; Braun et al, 2017 ; Click et al, 2019 ; Cooper et al, 2018 ; Kidd et al, 2016 ; Marshall et al, 2017 ; Minturn et al, 2021 ; Rosendale & Josephson, 2017 ; Roth et al, 2020 ; Salkind et al, 2019 ; Sawning et al, 2017 ; Stumbar et al, 2021 ; Ufomata et al, 2020 ; Underman et al, 2016 ; Vance et al, 2020 ; Ward-Gaines et al, 2021 ). Kidd and colleagues critiqued the limited effectiveness of ‘one-shot’ educational interventions, on which much of residency education relies, [which] may not necessarily result in sustained improvements” ( 2016 , p. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In First year medical student experiences with a clinical skills seminar emphasizing sexual and gender minority population complexity, 19 Biro, Song, and Nyhof-Young reported a qualitative evaluation study to explore how first-year medical students experienced a sexual and gender minority (SGM) clinical skills seminar. They found that recognizing the lived experiences of SGM community members, developing allies, and promoting faculty development are necessary elements of future curricular interventions in this area.…”
Section: E4 Major Contributionsmentioning
confidence: 99%
“…Response to "First year medical student experiences with a clinical skills seminar emphasizing sexual and gender minority population complexity" by Kumar and Hassan 44 acknowledged the previously published article by Biro et al 45 that explored limitations in medical training for the LGBTQ2S community. However, Kumar and Hassen advocated for further progress and reform for medical training to address the health requirements for sexual and gender minorities.…”
Section: Letters To the Editormentioning
confidence: 99%